A new species of the genus Tonoscolex Gates, 1933 (Clitellata: Megascolecidae) from India - Ahmed, Shakoor; Emiliyamma, K. G.; Marimuthu, Nithyanandam; Sajan, Sheikh; Julka, J. M. (Zootaxa, 2022)
Tonoscolex kalimpongensis Ahmed & Julka sp. nov. is described from Neora Valley National Park in the Kalimpong district of West Bengal, India. The new species is easily distinguished by the presence of one pair of spermathecal pores at intersegmental furrow 7/8. An updated checklist of the genus Tonoscolex and an identification key to the Indian Tonoscolex species are provided as well.